Genotypic characterization of Shiga toxin-producing Escherichia coli O157:H7 isolates in food products from china between 2005 and 2010. (April 2015) - Bai, Li; Guo, Yunchang; Lan, Ruiting; Dong, Yinping; Wang, Wei; Hu, Yujie; Gan, Xin; Yan, Shaofei; Fu, Ping; Pei, Xiaoyan; Xu, Jin; Liu, Xiumei; et al.
Abstract: Shiga toxin-producing Escherichia coli (STEC) O157 is an important foodborne pathogen. The aims of this study were to determine genetic relatedness of STEC O157 isolated from foods in China. STEC O157 isolates from food were characterized by virulence gene typing, antibiotyping, Multi-locus sequence typing (MLST), pulsed-field gel electrophoresis analysis (PFGE), Multi-locus variable number tandem repeat analysis (MLVA), and the single nucleotide polymorphism (SNP) clade typing. Of the 30 STEC O157 isolates analyzed, all isolates harbored eae, exhA, stx1 and/or stx2 genes with stx2c subtype predominating. By MLST, they were relatively homogenous with only 4 STs. PFGE and MLVA generated 22 pulsotyples and 23 patterns, respectively, which showed considerable diversity. Only one clade 8 isolate was detected. These results indicate that STEC O157 isolates from foods in China were heterogeneous. There was no correlation between genotypic characteristics and sources of isolates. Since different subtyping methods often give different discriminatory powers, the use of more than one subtyping approach is necessary in providing a more accurate picture of the genetic diversity of STEC O157. Four isolates were from ready-to-eat meat or salads, underscores the risk of infections. There is a need for surveillance of STEC O157 in foods and clinically and implementation of prevention strategies to prevent outbreaks of STEC O157 infections in China. Highlights: Genetic characterization of 30 STEC O157 isolates cultured from retail foods in China. All isolates harbored eae, exhA and stx2c is the predominant subtype of stx gene. Some ready to eat meat and salad were foods at high risk of STEC O157 contamination. STEC O157 isolates from China retail foods were considerable diversity with 22 pulsotyples by PFGE and with 23 patterns by MLVA. One clade 8 isolate was detected.